A Qualitative Study on Development of Enriching Performance Management System at a Pharma-Company - Muhammad A. Khan; Muhammad A. Hanif; Tehzeeb Sakina Amir (Institute of Business Management, 2018)
This case study aimed to develop a sample of enriching the performance management system using qualitative method. The job post of Import Executive in a pharma company has been selected as a sample. After taking consent from the management, a semi-structured interview approach with all related employees was undertaken. A comparison of existing performance management system was done with three other organizations of the same industry to provide a more comprehensive approach. Firstly, a systematic job evaluation was performed to transform traditional job description into competency based job description and implement job specific performance appraisal. This resulted in enrichment of performance management system. Peer evaluation and appraisal training for the supervisors have been suggested for a more comprehensive insight and a greater employee satisfaction with the performance management process.